Applications of fuzzy technology in civil engineering and construction management: the special issue in the 100th anniversary of Lotfi Zadeh - Liao, Huchang; Plebankiewicz, Edyta (Journal of Civil Engineering and Management, 2021)
In papers published in Journal of Civil Engineering and Management, many applications of fuzzy logic can be found. To commemorate the contributions of the fuzzy set theory proposed by Professor Lotfi Zadeh to the fields of civil engineering and construction management, seven papers were selected for this special issue. These papers combined fuzzy set theory with appropriate methods to solve specialized problems in the fields of civil engineering and construction management, and provided good insights for the applications of fuzzy technology in solving problems related to civil engineering and construction management.